2017
DOI: 10.1111/imig.12298
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Small Farming and Food Security in the Caribbean: Jamaica and St. Vincent and the Grenadines

Abstract: Long‐term and short‐term (seasonal) migrations from Caribbean countries have been strategies for enhancing the livelihoods and assets of individuals and families for many decades. The greatest challenges to food security are felt by the populations below the poverty level, most of whom are rural dwellers. Taking two Caribbean countries – Jamaica, and St. Vincent and the Grenadines, this article assesses whether in rural, characteristically small‐farming areas, the financial and social remittances resulting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Much of this research examines food purchase and not necessarily food production, begging the question of whether migrant remittances and savings contribute to semi‐subsistence production, and therefore food security for poorer, rural residents. One recent study comparing migrant‐sending families in Jamaica and St Vincent (Thomas‐Hope, ) found that migrant families in Jamaica have been able to increase small‐scale food production, but that they replaced production with food purchase in St Vincent. Understanding the dynamic between migration earnings and semi‐subsistence farming remains a clear gap in the migration–food security literature.…”
Section: Bringing South–south Migration To the Fore In Central Americmentioning
confidence: 99%
“…Much of this research examines food purchase and not necessarily food production, begging the question of whether migrant remittances and savings contribute to semi‐subsistence production, and therefore food security for poorer, rural residents. One recent study comparing migrant‐sending families in Jamaica and St Vincent (Thomas‐Hope, ) found that migrant families in Jamaica have been able to increase small‐scale food production, but that they replaced production with food purchase in St Vincent. Understanding the dynamic between migration earnings and semi‐subsistence farming remains a clear gap in the migration–food security literature.…”
Section: Bringing South–south Migration To the Fore In Central Americmentioning
confidence: 99%
“…In order to be able to influence development dynamics, it seems appropriate to look upon islands as complex socio-ecological systems. In island studies, this perspective is not so common [12][13][14]: Rather, there is a focus on particular problems such as food security [15], migration [16], or overgrazing [17]. Guiding local sustainable development means to understand the conditions under which socio-economic activities can support the quality of life and the income of the islanders while sustaining (or even improving) the quality and resilience of the natural environment.…”
Section: Heuristics and Methodsmentioning
confidence: 99%
“…Studies have shown that Caribbean farmers with land tenure, access to diverse markets and sources of income and support, see less negative effects on their food security and thus, cope better with extreme weather events [19,36,[60][61][62][63]]. Yet, studies in the Caribbean have mainly focused on Cuba, and the Caribbean Community (CARICOM)-to which Puerto Rico is not a part of [19,60,61,64,65]. It is important to note that the Caribbean is compose of islands of diverse landmasses, many of which are not sovereign and that are embedded in neocolonial relationships with former metropolis [21,22,27].…”
Section: Introductionmentioning
confidence: 99%